Data Centre Profile: The Provincial Health Data Centre of the Western Cape Province, South Africa - Boulle, Andrew; Heekes, Alexa; Tiffin, Nicki; Smith, Mariette; Mutemaringa, Themba; Zinyakatira, Nesbert; Phelanyane, Florence; Pienaar, Cara; Buddiga, Kasturi; Coetzee, Eduan; Van Rooyen, Renier; Dyers, Robin; et al. (International journal of population data science, 2019)
Introduction The Western Cape Provincial Health Data Centre (PHDC) consolidates person-level clinical data across government services, leveraging sustained investments in patient registration systems, a unique identifier, and maturation of administrative and clinical digital health systems. Objectives The PHDC supports clinical care directly through tools for clinicians which integrate patient data or identify patients in need of interventions, and indirectly through supporting operational and epidemiological analyses. Methods The PHDC is housed entirely within government. Data are processed from a range of source systems, usually daily, through distinct harmonisation and curation, beneficiation, and reporting processes. Linkage is predominantly through the unique identifier which doubles as a pervasive folder number, augmented by other identifiers. Further data processing includes triangulation of multiple data sources for enumerating health conditions, with assignment of certainty levels for each enumeration. Outputs include patient-specific email alerts, a web-based consolidated patient clinical viewing platform, filterable line-listings of patients with specific conditions and associated characteristics and outcomes, management reports and dashboards, and data releases in response to operational and research data requests.  Strict architectural, administrative and governance processes ensure privacy-protection. Results In the past decade 8 million unique people are recorded as having sought healthcare in the provincial public sector health services, with current utilisation at 15 million attendances or admissions a year.  Cross-sectional enumeration of health conditions includes over 430 000 people with HIV, 500 000 with hypertension, 235 000 with diabetes. 110 000 pregnancies and 54 000 patients with tuberculosis are enumerated annually. Each year over 50 data requests are processed for internal and external requesters in accordance with data request and release governance processes. Conclusions The single consolidated environment for person-level health data in the Western Cape has created new opportunities for supporting patient care, while improving the governance around access to and release of sensitive patient data.